Varicose Vein Sclerotherapy Using Polidocanol for Chronic Non-Healing Leg Ulcer: A Case Report from Muhimbili National Hospital (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Background: Chronic venous ulcers represent the most severe manifestation of chronic venous insufficiency and are associated with significant morbidity, particularly when longstanding and untreated. In low-resource settings, limited access to advanced vascular interventions often results in prolonged disease duration and poor outcomes. Minimally invasive techniques such as ultrasound-guided foam sclerotherapy offer a potential alternative for definitive management.Case Presentation: We report a 26-year-old male who presented with a 10-year history of left lower limb swelling and a chronic non-healing ulcer around the ankle. The lesion initially developed as a raised skin lesion and progressed into an ulcer associated with intermittent bleeding. Clinical examination revealed varicose veins and localized swelling of the left lower limb. Duplex ultrasound demonstrated dilatation of the small saphenous vein with an incompetent sapheno-popliteal junction and multiple incompetent perforator veins, with no evidence of deep venous thrombosis.Intervention: The patient underwent ultrasound-guided polidocanol foam sclerotherapy targeting the incompetent venous segments.Outcome: Following treatment, progressive ulcer healing was observed, culminating in complete epithelialization and resolution of symptoms. No complications were reported.Conclusion: This case demonstrates that ultrasound-guided polidocanol foam sclerotherapy can achieve complete healing of longstanding venous ulcers by addressing underlying venous reflux. It also highlights the feasibility and effectiveness of this minimally invasive technique in a low-resource setting and supports its broader adoption in similar healthcare environments.